Life-Cycle Wages and Human Capital Investments: Selection and Missing Data - Gobillon, Laurent; Magnac, Thierry; Roux, Sébastien (Review of Economic Studies, 2025)
Abstract We derive wage equations with individual-specific coefficients from a structural model of human capital investment over the life-cycle. This model allows for interruptions in labour market participation and deals with missing data and attrition problems. We propose a new framework that deals with missingness at random and is based on factor decompositions that allow for flexible control of selection. Our approach leads to an interactive effect wage specification, which we estimate using long administrative panel data on male wages in the private sector in France. A structural function approach shows that interruptions negatively affect average wages. Interestingly, they also negatively affect the inter-decile range of wages after twenty years. This is only partly due to the fact that interruptions are endogenous.